2014
DOI: 10.1177/1059840514543525
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of Documenting Schoolchildren’s Psychosocial Health

Abstract: The aim of this study was to explore school nurses' experience of challenges related to documenting schoolchildren's psychosocial health in Sweden. Six focus group discussions were carried out. Areas for discussions included questions about situations, especially challenging to document as well as what constrains and/or facilitates documenting psychosocial health problem issues. Qualitative content analysis was used for interpreting the data. The analysis resulted in one overarching theme: having to do one's d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 19 publications
(27 reference statements)
0
23
0
Order By: Relevance
“…The training of school personnel is important, but Alexander et al (2005) show that training initiatives are not enough: it is also necessary to change attitudes around children living with domestic violence (cf. Chanmugam and Teasley 2014;Clausson et al 2015;Dufva 2001;Odenbring et al 2015). The professionals requested clear guidelines about how an issue such as domestic violence is to be managed in the school.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The training of school personnel is important, but Alexander et al (2005) show that training initiatives are not enough: it is also necessary to change attitudes around children living with domestic violence (cf. Chanmugam and Teasley 2014;Clausson et al 2015;Dufva 2001;Odenbring et al 2015). The professionals requested clear guidelines about how an issue such as domestic violence is to be managed in the school.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that they tend to avoid documenting psychosocial problems and problems related to the family in student health records. They may be afraid of stigmatizing the child or the parents, or of meeting the parents (Clausson et al 2015;Münger and Markström 2018).…”
Section: Previous Researchmentioning
confidence: 99%
“…The structure of the health record, which emphasises physical health, made it more difficult to document sensitive issues, although doing so was considered important. [18] Earlier studies of school nurses have shown the importance of building a trusting relationship with adolescents. It was important that the school nurse was present and had an "open door" for counselling and discussion.…”
Section: Introductionmentioning
confidence: 99%
“…The SHS is led and managed by the principal of the school and includes professions such as school nurses, school physicians, psychologists, guidance counselors and special education teachers. [1] In upper-secondary school, the school nurse invites each student aged [16][17][18][19] to a health dialogue during the first year with the aim of promoting and strengthening the health of the student. [2] Various health and lifestyle questionnaires have been developed and used during the health dialogue.…”
Section: Introductionmentioning
confidence: 99%
“…A inductive content analysis was conducted (Elo & Kyngäs, 2008). Specifically, meaning units, codes, and themes accompanied by the supporting transcribed narrative were produced to capture mothers' experiences and perspectives (Clausson, Berg, & Janlöv, 2015).…”
Section: Discussionmentioning
confidence: 99%